Risk of contralateral lower limb amputation and death after initial lower limb amputation – a population-based study. Issue 10 (October 2018) - Huseynova, K.; Sutradhar, R.; Booth, G.L.; Huang, A.; Ray, J.G.
Abstract: Background: Lower limb amputation (LLA) is a complication of lower limb atherosclerosis, infection and tissue gangrene. Following ipsilateral LLA, the risk of major amputation of the contralateral limb or of death is unknown. The aim of this study was to determine the incidence of a contralateral major LLA, comparing those with a non-malignant/non-traumatic ipsilateral major vs. ipsilateral minor LLA. Methods: We used pre-existing linked administrative health databases for the study. Data were provided by the Institute for Clinical Evaluation Sciences (ICES), Toronto, Ontario. This is a retrospective population-based cohort study across Ontario, Canada, 2002–2012. Cause-specific Cox regression models were used to obtain hazard ratios. Cumulative incidence functions were used to calculate the risk of contralateral major LLA and the risk of the competing event death. Individuals who did not survive at least 30 days after their first ipsilateral LLA were excluded since they were ineligible to have a contralateral LLA. Results: 5, 816 adults underwent an ipsilateral major and 4, 143 an ipsilateral minor LLA. The incidences of contralateral major LLA were 4.8 and 2.2 (adjusted HR 2.41, 95% CI 2.04–2.84) after ipsilateral major and minor LLA, respectively. Incidence of death was 18.9 and 11.4 (adjusted HR 1.22, 95% CI 1.13–1.31) following ipsilateral major and minor LLA, respectively. Conclusion: There is high incidence of a contralateral major LLA and even higher risk of death following the ipsilateral LLA. Healthcare professionals should develop strategies for contralateral limb preservation in individuals with existing ipsilateral LLA.